2013
DOI: 10.1039/c3nr03153e
|View full text |Cite
|
Sign up to set email alerts
|

Highly dispersed palladium nanoparticles anchored on UiO-66(NH2) metal-organic framework as a reusable and dual functional visible-light-driven photocatalyst

Abstract: Proper design and preparation of high-performance and stable dual functional photocatalytic materials remains a significant objective of research. In this work, highly dispersed Pd nanoparticles of about 3-6 nm in diameter are immobilized in the metal-organic framework (MOF) UiO-66(NH₂) via a facile one-pot hydrothermal method. The resulting Pd@UiO-66(NH₂) nanocomposite exhibits an excellent reusable and higher visible light photocatalytic activity for reducing Cr(vi) compared with UiO-66(NH₂) owing to the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
209
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 442 publications
(217 citation statements)
references
References 74 publications
8
209
0
Order By: Relevance
“…It shows that the lower pH value results in better photocatalytic performance. This catalyzed effect of the acidified pH values is consistent with the previously reported results that the photocatalytic reduction of Cr(VI) is an acid‐catalyzed behavior 36, 37, 38. At pH 2–4, the predominating species of chromium is Cr 2 O 7 2− , and the Cr(VI) reduction reaction could be expressed as follows36 Crnormal2normalOnormal72+14H++6e2Cr3++7Hnormal2O 2Hnormal2O+2h+normalHnormal2normalOnormal2+2H+ …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It shows that the lower pH value results in better photocatalytic performance. This catalyzed effect of the acidified pH values is consistent with the previously reported results that the photocatalytic reduction of Cr(VI) is an acid‐catalyzed behavior 36, 37, 38. At pH 2–4, the predominating species of chromium is Cr 2 O 7 2− , and the Cr(VI) reduction reaction could be expressed as follows36 Crnormal2normalOnormal72+14H++6e2Cr3++7Hnormal2O 2Hnormal2O+2h+normalHnormal2normalOnormal2+2H+ …”
Section: Resultssupporting
confidence: 92%
“…With the increase of irradiation time, the absorption peak at 540 nm ascribed to the DPC–Cr(VI) complex decreases gradually, and it almost disappears after 45 min, which demonstrates the photocatalytic reduction of Cr(VI) over NH 2 –MIL‐88B (Fe). Previous studies reported that the pH value of the solution had a great effect on the reduction rate of aqueous Cr(VI) over photocatalyst 36, 37. To investigate the influence of pH value on the photocatalytic reduction of Cr(VI), controlled experiments of photocatalytic reduction of Cr(VI) over NH 2 –MIL‐88B (Fe) have been carried out with different pH values.…”
Section: Resultsmentioning
confidence: 98%
“…1. These materials are known to be very stable and have been intensively studied for a whole range of applications [13][14][15][16][17][18]. A synergic combination of experimental XRPD and EXAFS measurements and theoretical ab initio simulations proved necessary to reveal the correct geometrical structure of UiO-66, as reported by Valenzano et al [19].…”
Section: Introductionmentioning
confidence: 85%
“…The high Fermi energy level of noble-metal NPs can efficiently separate photoexcited electron-hole pairs of the photocatalyst, which could improve the photoactivity toward target reactions [17][18][19][20]. It has been previously demonstrated that MOFs are particularly promising as supports for noble-metal NP immobilization because of their ultrahigh surface area and moderate thermal stability, which are important for controlling the limited growth of metal NPs and producing highly reactive monodispersed metal NPs [21]. Therefore, the integration of noble-metal NPs with MOF photocatalysts in an appropriate manner would further improve the photocatalytic activity of MOFs.…”
Section: Introductionmentioning
confidence: 99%